Magnetic resonance imaging-based diagnosis of aortitis preceding development of a thoracic aneurysm in a patient with giant cell arteritis: a case report. Issue 4 (12th April 2022) - Lutter, Georg; Puehler, Thomas; Röcken, Christoph; Both, Marcus
Abstract: Background: Inflammatory manifestation in the aortic arch can be a complication of giant cell arteritis (GCA), potentially requiring surgical therapy in the case of aneurysmatic dilatation. Case summary: We report the case of a 73-year-old female patient with GCA in whom a typical appearance of arteritis was visualized on magnetic resonance imaging of the superficial temporal arteries. Additionally, ectasia (4.7 cm) of the ascending aorta with a mural rim of increased contrast media uptake was detected at the time of the initial diagnosis, which is an indicator of aortitis. While the diameter had only minimally increased in a computed tomography angiography (CTA) examination after 8 months, a subsequent CTA revealed an increased diameter of 5.8 cm and maximum at the level of the ascending aorta another 22 months later, indicating urgent surgery to replace the ascending aorta. Discussion: Magnetic resonance imaging can detect silent, generalized manifestations of GCA such as severe aortitis, which may possibly lead to aneurysmatic dilatation, urging closer follow-up imaging. Detection of the ongoing process and subsequent follow-up imaging protects patients by avoiding rupture.